2016
DOI: 10.4103/0974-9233.171779
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in two Saudi patients with congenital retinal dystrophy

Abstract: To report novel mutations in two Saudi children with clinical features of Leber congenital amaurosis (LCA) and Alström syndrome. Case reports. Case 1 was a child with phenotypic features of LCA including oculodigital sign, bilateral enophthalmos, nystagmus, pale disc, and retinal changes. Direct sequencing of the coding sequence of GUCY2D revealed a missense mutation affecting highly conserved position (c. 743C > T; p.S248 L). Case 2 describes a girl with marked nystagmus, photophobia, and retinal changes in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…However, as of now, only a few studies on AS patients are published from Arab world (Chakroun et al, 2016). From Saudi Arabia, only three published studies are listed in PUBMED (Aldahmesh et al, 2009, Safieh et al, 2016, Bakar et al, 2017). Bakar AA et al, (Bakar et al, 2017) has described a homozygous frameshift mutation leading to a premature termination codon (p. Arg4052Glyfs ∗ 2) in ALMS1 gene in an AS patient presenting clinical manifestations like diabetic ketoacidosis, hearing loss and blindness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as of now, only a few studies on AS patients are published from Arab world (Chakroun et al, 2016). From Saudi Arabia, only three published studies are listed in PUBMED (Aldahmesh et al, 2009, Safieh et al, 2016, Bakar et al, 2017). Bakar AA et al, (Bakar et al, 2017) has described a homozygous frameshift mutation leading to a premature termination codon (p. Arg4052Glyfs ∗ 2) in ALMS1 gene in an AS patient presenting clinical manifestations like diabetic ketoacidosis, hearing loss and blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Bakar AA et al, (Bakar et al, 2017) has described a homozygous frameshift mutation leading to a premature termination codon (p. Arg4052Glyfs ∗ 2) in ALMS1 gene in an AS patient presenting clinical manifestations like diabetic ketoacidosis, hearing loss and blindness. Safieh et al (2016) reported two novel mutations including a missense mutation (p.S248L) and protein truncation mutation (p.S2814 *) in AS patients from 2 different families with a history of consanguinity and congenital retinal dystrophies. Aldahmesh et al (2009) identified four novel homozygous pathogenic mutations in 4 sporadic AS cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding reports from Saudi Arabia, to date, 2 report cases by Aldahmesh et al and Abu-Safieh et al have reveled 4 and 2 novel mutations respectively. [ 7 , 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…By using whole-exome sequencing, earlier our group found causative rare biallelic mutations in the ALMS1 gene in exon 8 (T376S in exon 5, and S909 * ) and exon 10 (R2721 * ) among AS patients from two other unrelated Saudi families ( 28 ). These truncating mutations at residues S909 and R2721 possibly create an unstable protein due to loss of CC domain and ALMS motif on the C-terminal end which led to intracellular truncated protein degradation ( 31 ). Another retrospective study from Saudi Arabia has reported the identification of 10 ALMS1 different mutations (E3649 * , Q2648 * , p.E913Sfs * 20, p.Ser2102 * , p.Arg2928 * , p.Ser2102 * , p.Arg2722 * , p.P3911QfsX16, p.Ser908 * , IVS18-3A>T) in 19 Alström cases presenting different ophthalmic phenotypes from 13 Saudi families.…”
Section: Discussionmentioning
confidence: 99%